Penggunaan Internet of Things (IoT) dalam Industri Pembinaan di Malaysia - Sabri, Syafiqah; Yahya, Mohd Yamani (Research in Management of Technology and Business, 2020)
The Internet of Things (IoT) is an emerging technology in the construction industry, especially in Malaysia. There are concerns and problems resulting from the use of IoT, such as the lack of exposure to emerging technology and the use of outdated methods in the construction industry, and the inability to adapt IoT to the lives of the public and businesses when they are aware of its presence. The goal of this study is therefore to identify the use of IoT in the construction industry and to identify the challenges of using IoT in construction, as well as suggestions to promote the use of IoT in the construction industry. This research used qualitative method, which was interviewing method, to accomplish these objectives. Respondents to this study were three Consultants from Johor Bahru, Johor. The collected data collection was analysed using the content analysis technique. The findings indicated that the use of smartphones is the most used IoT technology in the construction industry, as well as the safety risk of IoT use. In addition, the plan to promote the use of IoT in the construction industry is made by cooperation with other businesses. In conclusion, this study would help the construction industry by making progress in today’s use of IoT technology.